1990
DOI: 10.1095/biolreprod42.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Ethanol Diet on Pituitary-Testicular Function of the Rat1

Abstract: We studied the effects of a 6% ethanol liquid diet administered for 5 wk on the pituitary-gonadal function of adult male rats. Because ethanol is known to reduce body weight, we used sucrose-fed animals as controls. No significant differences in body, testis, or prostate weights were found between the rats exposed to ethanol and their sucrose-fed controls at the end of the 5-week treatment. Seminal vesicle weights decreased significantly (p less than 0.05) in the ethanol-treated group. Serum and testicular tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
0
3

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 25 publications
5
52
0
3
Order By: Relevance
“…The reduced serum testosterone level may be due to defects in various parts of the hypothalamo-hypophyseal-testicular hormone axis, such as the inhibition of LHRH release [36] and thus low LH [1,2], and at the level of the Leydig cells by reducing LH receptors [37][38][39] and steroidogenic enzyme [3]. In general, the reduced levels of both LH and testosterone are suggestive of hypogonadotropic hypogonadism and an impaired feed back system due to ethanol treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced serum testosterone level may be due to defects in various parts of the hypothalamo-hypophyseal-testicular hormone axis, such as the inhibition of LHRH release [36] and thus low LH [1,2], and at the level of the Leydig cells by reducing LH receptors [37][38][39] and steroidogenic enzyme [3]. In general, the reduced levels of both LH and testosterone are suggestive of hypogonadotropic hypogonadism and an impaired feed back system due to ethanol treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The decreased serum LH and its receptors in Leydig cells [38,39] may be responsible for the decreased activity of NADPH generating enzymes, as LH is the principal regulating factor in Leydig cellular structure and function [41]. In vitro studies by Akane et al [3] have suggested that ethanol (1, 5, 20 and 100 mM) has a direct inhibitory effect on Leydig cellular 3/3-HSD and 17, 20 lyase.…”
Section: Resultsmentioning
confidence: 99%
“…Also, chronic ethanol exposure for 30 days has been shown to cause testicular atrophy and accessory reproductive organ dysfunction in adult male rats [3]. Another study showed that ethanol exposure decreases male reproductive ability through the reduction of testosterone production and the suppression of spermatogenesis and steroidogenesis [13].In testicular germ cells, pituitary adenylate cyclase activating polypeptide (PACAP) has been shown to stimulate cAMP production and to contribute to spermatogenesis [5,9]. PACAP has considerable homology with secretin, glucagon, vasoactive intestinal peptide, and growth hormone releasing hormone [10,11].…”
mentioning
confidence: 99%
“…Also, we confirmed that ethanol exposure significantly reduced serum testosterone levels in adult male rats. Previous studies demonstrated that ethanol suppresses male reproductive activity through the inhibition of testosterone release by reduction of LH secretion from the pituitary gland [23,25]. Also, it has been shown that the reduction of LH levels by ethanol decreases testosterone release through the inhibition of steroidogenic acute regulatory protein expression in testes [14].…”
Section: Inhibitory Effects Of Ethanol Treatment On Pac 1 Receptor Mrmentioning
confidence: 99%
“…In particular, ethanol decreases male reproductive ability through the reduction of testosterone production by inhibition of luteinizing hormone (LH) release from pituitary gland [23,25]. In males, LH stimulates testosterone production through cAMP activation in testicular Leydig cells.…”
mentioning
confidence: 99%